Infrastructure in India's development - Urban transport - Sibal, Vinod (2001)
Urban transport is an important basic infrastructure on which the economic growth of cities depends. The demands of this sector are growing fast. This fact coupled with provision of insufficient mass transport and road infrastructure facilities and inadequate regulation has resulted in high congestion levels on roads, low journey speeds, high energy consumption on transport and increased vehicular emissions and accidents. The scenario for the future is bleak unless policy interventions are made to augment infrastructure in a planned way. This article attempts to peek into future urban transport scenario 20 years hence-both under assumptions of Business As Usual (BAU) and under implementation of suggested policy interventions. - Reproduced
Keywords: Infrastructure development - India; Transport - India; Urban transport - India; Urban transport